2008
DOI: 10.1002/nag.763
|View full text |Cite
|
Sign up to set email alerts
|

Bearing capacity factor Nc under ϕ=0 condition for piles in clays

Abstract: SUMMARYBearing capacity factor N c for axially loaded piles in clays whose cohesion increases linearly with depth has been estimated numerically under undrained ( = 0) condition. The study follows the lower bound limit analysis in conjunction with finite elements and linear programming. A new formulation is proposed for solving an axisymmetric geotechnical stability problem. The variation of N c with embedment ratio is obtained for several rates of the increase of soil cohesion with depth; a special case is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…Note that the present N γ solutions are found to be slightly lower (better) than the upper bound solution given by Lyamin et al (2007) based on the threedimensional finite element limit analysis. In Table 1, the obtained magnitudes of N c for ϕ ¼ 0 ○ but with different values of m, were also compared with (i) the solutions of Khatri and Kumar (2008), (ii) the solutions of Houlsby and Martin (2003) based on the method of the stress characteristics, and (iii) the upper bound solution of Kusakabe et al (1986) based on rigid blocks mechanism. The present upper bound values of N c are found to be slightly lower than the upper bound solution given by Kusakabe et al (1986).…”
Section: Results and Comparisonmentioning
confidence: 99%
“…Note that the present N γ solutions are found to be slightly lower (better) than the upper bound solution given by Lyamin et al (2007) based on the threedimensional finite element limit analysis. In Table 1, the obtained magnitudes of N c for ϕ ¼ 0 ○ but with different values of m, were also compared with (i) the solutions of Khatri and Kumar (2008), (ii) the solutions of Houlsby and Martin (2003) based on the method of the stress characteristics, and (iii) the upper bound solution of Kusakabe et al (1986) based on rigid blocks mechanism. The present upper bound values of N c are found to be slightly lower than the upper bound solution given by Kusakabe et al (1986).…”
Section: Results and Comparisonmentioning
confidence: 99%
“…The standard constraints of the LB requirements are summarized below here. Readers are referred to Tang et al and Khatri and Kumar for the details of coefficients associated with vectors and matrices of the standard constraints.…”
Section: D Axisymmetric Lb Felamentioning
confidence: 99%
“…It can be observed that the nonlinear term of r in Equation makes it not possible for the stress state to satisfy the equilibrium equations in every material point within triangular elements by enforcing these at their corner nodes. To derive the equilibrium constraints of triangular elements, this paper adopts the concept of enforcing the equilibrium equations at the centroid of the element as proposed by Khatri and Kumar and Tang et al Thus, the first set of the equilibrium constraint on the unknown nodal stress can be obtained by substituting Equation into Equation and imposing at the centroid of each element as []Aitaliceq{}σ={}Bitaliceq …”
Section: D Axisymmetric Lb Felamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, by using the method of characteristics, Siva Reddy et al (1991) have obtained the solutions for both strip and circular smooth footings for the cases of footing placed at very shallow depths from ground surface. More recently, by using the lower bound limit analysis in conjunction with finite elements, the bearing capacity factor N c for several rates of increase of cohesion with depth has been estimated by Khatri and Kumar (2009) for axially loaded piles. In the existing investigations, for layered soils, the effect of an increase of soil cohesion with depth has not been addressed in detail.…”
Section: Introductionmentioning
confidence: 99%